“Baby, you can drive my car”: means of transportation in a long dream series - Schredl, Michael (International journal of dream research, 2020)
Using transportation means like cars, public transportation is an important part of modern life style. Thus, it is not unexpected that transportation also plays a significant role in dreams. In a long series (N = 11,463 dreams) of one dreamer (single-case study) about 16% of the dreams included some form of transportation. The dreamer who is driving cars very rarely, dreamed more often about being a co-driver than a driver - in contrast to persons who drive a car regularly, supporting the continuity hypothesis of dreaming. On the other hand, several dreams were “creative”, i.e., don’t reflect any actual waking-life experiences of the dreamer, for example, traveling in a spaceship or submarine. Car trouble dreams were frequent (40% of the car driving dreams) even though the dreamer never experienced car trouble in waking life, e.g., malfunctioning brakes. This supports the idea of Patricia Garfield that this dream type is metaphorically linked to feelings of not being in control in waking life. Very interesting topics for future research would be studying the relationship of “creative” dreams, i.e., dreams that did not reflect directly the actual waking-life experience of the dreamer, and his or her waking life and the possible metaphoric link between car trouble dreams and waking-life stress.
Gesehen am 07.04.2020